Grammatical errors in writing Narrative text made by Ninth Grade Students of SMPN 1 Kuta Buluh - Yunanda, Fachri; Liandri, Vanessa; Simanjuntak, Lestari; Kembaren, Suci Lestari; Lubis, Bambang Nur Alamsyah; Asrul, Nurmahyuni (English Language Teaching Prima Journal (ELT), 2023)
The purpose of this study was to identify the different types of errors that ninth-grade students at SMPN 1 Kuta Buluh, Tanah Karo committed when writing narrative texts during the academic year 2022–2023. There were 28 students in this study. The author used a qualitative descriptive approach. On Friday, May 19, 2023, an offline investigation was conducted. The researchers looked into the narrative text writing errors made by the students. The categorization of student writing errors was the study's main goal. The Surface Strategy Taxonomy analysis of the results revealed 40 mistakes in the students' narrative text. 11 addition mistakes totaling 27.5% were made, as were 20 omission mistakes totaling 50%, 7 misformation mistakes totaling 17.5%, and 2 misordering mistakes totaling 5%. The most typical mistake is omission (20).